1976
DOI: 10.1128/aac.9.6.962
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Staphylococcus aureus and Staphylococcus epidermidis to 65 Antibiotics

Abstract: The susceptibilities of 36 recent isolates of Staphylococcus aureus and 35 recent isolates ofStaphylococcus epidermidis were determined against each of 65 antimicrobial agents and against two of them in combination. Rifampin was the most active of all the agents tested against both S. aureus and S. epidermidis. Among the penicillins, cloxacillin, dicloxacillin, and nafcillin were most active, although benzylpenicillin and phenoxymethyl penicillin were more active against susceptible strains. Cephaloridine was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(58 citation statements)
references
References 7 publications
3
54
0
1
Order By: Relevance
“…Rifampin never achieved a bactericidal effect in either phase. While rifampin has usually been considered an antistaphylococcal bactericidal agent (28,35,41), some authors have reported results consistent with our own (3, 9, 17). In contrast, levofloxacin reached a potent killing rate in the log phase and it also showed bactericidal activity in the stationary phase, although higher concentrations than those for the exponential phase were required.…”
Section: Discussionsupporting
confidence: 81%
“…Rifampin never achieved a bactericidal effect in either phase. While rifampin has usually been considered an antistaphylococcal bactericidal agent (28,35,41), some authors have reported results consistent with our own (3, 9, 17). In contrast, levofloxacin reached a potent killing rate in the log phase and it also showed bactericidal activity in the stationary phase, although higher concentrations than those for the exponential phase were required.…”
Section: Discussionsupporting
confidence: 81%
“…However, most of the standard in vitro studies have shown little or no difference in the anti-staphylococcal activity of those newest cephalosporins in comparison with other cephalosporins that have been available for several years or more (5,15,17). Previous studies (3,14) have already established a certain correlation between the susceptibility of various cephalosporins to staphylococcal ,B-lactamase and the magnitude of the effect of the inoculum size when those same cephalosporins were tested against large and small inocula of staphylococci.…”
mentioning
confidence: 99%
“…However, most of the standard in vitro studies have shown little or no difference in the anti-staphylococcal activity of those newest cephalosporins in comparison with other cephalosporins that have been available for several years or more (5,15,17 …”
mentioning
confidence: 99%
“…The treatment of extremity trauma can be complicated by polymicrobial infections and systemic antibiotic treatment that can be toxic to organ systems [6,11,13,35,56,58]. Localized antimicrobial drug delivery systems, including biomaterial carrier matrices and coatings on implants, have become a focus to combat biofilm formation and infection for both preventive and treatment strategies [1,7,13,27,29,43,49,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The five coating-type groups (12 catheters in six mice) included uncoated wires; uncoated wires with codelivery of antibiotic solution (1 lg/mL vancomycin; 16 lg/mL amikacin); phosphatidylcholine-only coated; AV-combination coated; and A-coated. Amikacin was chosen as a single high-dose antibiotic because of its activity against S aureus as well as Gram-negative bacteria [58]. Two catheters from the same experimental group were implanted into the dorsa of each mouse bilaterally, one each on the right and left side of the spine, and then inoculated with a polymicrobial mixture of 10 5 CFUs of S aureus (UAMS-1) and 10 4 CFUs of P aeruginosa (Schroeter) Migula (ATCC 1 27317 TM , Manassas, VA, USA) directly into the lumen of the catheter.…”
Section: In Vivo Biofilm Inhibitionmentioning
confidence: 99%